A case study on dome structure of composite structural insulation panels with ANSYS simulations - Liang, Chunhang; Zhu, Liming (Frontiers in Materials, 2022)
Thin-shell dome structures are conventionally built with concrete. However, the building process is time-consuming and of high labor cost. Composite Structural Insulation Panels (CSIPs) have recently been regarded to be suitable for large-span civil structures, in terms of its light weight, easy processing, and mass production. Hence, this paper explores the feasibility of CSIPs domes applied in large-span dome structures. Compared with the performance of thin-shell concrete domes, the stiffness, strength, and stability of CSIPs domes are studied by means of refined finite element analysis. Results demonstrate CSIPs dome possesses good dynamic performance, bears larger nonlinear loads, and even copes with stress loads under earthquakes. Moreover, the stiffness should be handled in the onsite applications to fulfil the safety requirements.